2020
DOI: 10.3390/ma13040813
|View full text |Cite
|
Sign up to set email alerts
|

Residual Compressive Strength of Short Tubular Steel Columns with Artificially Fabricated Local Corrosion Damage

Abstract: Corrosion is considered as one of the main factors in the structural performance deterioration of steel members. In this study, experimental and numerical methods were used to assess the reduction in compressive strength of short tubular steel columns with artificially fabricated local corrosion damage. The corrosion damage was varied with different depths, heights, circumferences, and locations along the column. A parametric numerical study was performed to establish a correlation between the residual compres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Therefore, it is necessary to investigate the failure mechanism and ultimate strength of the corroded steel CHS bridge piers under the lateral cyclic loads. In addition, Kim et al (2021), Toledo et al (2020), and Dao et al (2018) have also indicated that due to the accumulation of dust and moisture at the junction of steel bridge piers and foundations, the end of bridge piers is more susceptible to corrosion damage than other parts, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the failure mechanism and ultimate strength of the corroded steel CHS bridge piers under the lateral cyclic loads. In addition, Kim et al (2021), Toledo et al (2020), and Dao et al (2018) have also indicated that due to the accumulation of dust and moisture at the junction of steel bridge piers and foundations, the end of bridge piers is more susceptible to corrosion damage than other parts, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, debe aplicarse correctamente, caso contrario, se puede acelerar la corrosión al presentar deslaminaciones o ampollas. La corrosión genera una pérdida de masa, principalmente en la reducción del área de la sección transversal y aunque sea muy baja, puede reducir la resistencia del material y llegar a generar una falla [3,4].…”
Section: Introductionunclassified
“…Buckling is a classic mechanical problem, the concept of which was introduced by Euler (Euler, 1744). Over the years, buckling analysis has found wide application, including in civil engineering (Śledziewski & Górecki, 2020;Toledo et al, 2020), mechanical engineering (Czechowski et al, 2020;Kubit et al, 2019) or the maritime industry (Corigliano et al, 2019;Shen et al, 2020). Currently, there is a renewed interest in buckling, in particular in applications in composite structures (Rozylo et al, 2020;Schilling & Mittelstedt, 2020;Xu & Wu, 2008) or micro and nano technologies (Barretta et al, 2019;Chandra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%